THE EFFECT OF ADMINISTERING AFRICAN BITTER LEAF EXTRACT ON SPERMATOGENIC CELLS OF HYPERGLYCEMIC WISTAR RATS - Kartana, Kartana; Tahalele, Paul L; Suwasanti, Niluh (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2021)
Introduction: Diabetes is still a world health problem that can cause many complications.Male infertility is one of the diabetic complications. This condition is caused by oxidativestress in diabetic patients. African bitter leaf is believed to contain an antioxidant compoundthat can repair male infertility. Purpose: This study aims to determine the effect of administering African bitter leaf extracton spermatogenic cell count in hyperglycemic Wistar rats. Method: This study use Rattus norvegicus as an animal model, which was administrated withalloxan to induce hyperglycemic. P0 group were given Na CMC 0,1%, Control group were given glibenclamide 0,63/kg bodyweight for 14 days. 100mg/kg bodyweight (P1), 200mg/kg (P2), and 400mg/kg (P3) of African bitter leaf extract were administrated for 14 days. In theend, the animals were sacrificed, and testicle histopathologic sections were made. Results: Significant result (P<0,05) comparing spermatogonium, primary spermatocyte, andspermatid count between groups. Post-hoc test shows the significant result on comparison ofprimary spermatocyte and spermatid count between P0 and P1.Conclusions: There is an effect of bitter leaf extract administration on spermatogenic cellcount in hyperglycemic Wistar rats. The best improvement can be observed in the P1 group,administered with 100mg/kg bodyweight African bitter leaf.